Investigation of the curing state of ethylene/vinyl acetate copolymer (EVA) for photovoltaic applications by gel content determination, rheology, DSC and FTIR. (July 2016) - Jaunich, Matthias; Böhning, Martin; Braun, Ulrike; Teteris, Gundars; Stark, Wolfgang
Abstract: The cure behaviour of a specific ethylene vinyl acetate material as used for encapsulation of photovoltaic modules was analysed by rheometer, differential scanning calorimetry and Fourier transform infrared spectroscopy to test for a suitable replacement for the laborious determination of gel content. The results show that all applied methods are capable of describing the effects of the cross-linking process. Some provide results very similar to those yielded by analysis of the insoluble content, but the question remains as to whether indirect methods should be preferred over the direct measurement of physical properties, e.g. as performed by the curemeter. A material stored for one year was also tested to demonstrate the effect of extended storage on cure behaviour and how this is detected by different methods. This complements the other methods, which were clearly able to detect the different cure behaviour of the aged EVA, whereas determination of the gel content could not.